Warrants for reconstruction: Christian hegemony, white supremacy - Hill Fletcher, Jeannine (Journal of ecumenical studies, 2016)
Discussions of religious pluralism have yet to consider how theologies of superiority might be linked with racist ideologies. Tracing historical precedents of Christian theologies of religious supremacy that inform racist practices and legislation, this essay argues the need for reconstructing Christian theologies of religious difference with anti-racist and anti-supremacist tools.